(untitled) (Web of Humanities: Journal of Social Science and Humanitarian Research, 2024)
This article explores the various methodologies employed in teaching mathematics in primary education. It delves into the theoretical foundations, practical applications, and effectiveness of different teaching strategies. The study emphasizes the importance of a solid mathematical foundation in early education and provides insights into best practices for educators.